Facile synthesis of highly conductive PEDOT:PSS via surfactant templates. Issue 11 (21st February 2019) - Sakunpongpitiporn, Phimchanok; Phasuksom, Katesara; Paradee, Nophawan; Sirivat, Anuvat
Abstract : The electrical conductivity of 1879.49 ± 13.87 S cm −1 was achieved for PEDOT:PSS, which is the highest value reported to date. Abstract : Poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) nanoparticles in powder form with high electrical conductivity were synthesized via chemical oxidative polymerization. In addition, the effects of EDOT : PSS weight ratio, EDOT : Na2 S2 O8 mole ratio, and surfactant concentration and type, namely hexadecyltrimethylammonium bromide (CTAB), sodium dodecylsulfate (SDS), and polyoxyethylene octyl phenyl ether (Triton X-100) on the properties of PEDOT:PSS were investigated. For the effect of EDOT : PSS weight ratio, at the EDOT : Na2 S2 O8 mole ratio of 1 : 1, the EDOT : PSS weight ratio of 1 : 11 was the optimal condition to obtain electrical conductivity of 999.74 ± 10.86 S cm −1 due to the high amount of PSS − and SO4 2− available to interact with the PEDOT chain with a low % PSSNa. For the effect of EDOT : Na2 S2 O8 mole ratio, at the EDOT : PSS weight ratio of 1 : 11, the EDOT : Na2 S2 O8 mole ratio of 1 : 2 was the best condition as it provided the highest dopant (PSS − and SO4 2− ) amount, while the % PSSNa was relatively low. For the effect of surfactant type and concentration, at the EDOT : PSS weight ratio of 1 : 11 and EDOT : Na2 S2 O8 mole ratio of 1 : 2, Triton X-100 at 2.5CMC provided electrical conductivity higher than with CTAB and SDS. The thermal stability of PEDOT:PSS obtained from various conditions was investigated, and PEDOT:PSS without surfactant showed the highest thermal stability since it produced the highest char yield. In this study, the highest electrical conductivity of PEDOT:PSS, which was obtained in the presence of Triton X-100 to reduce the PSSNa amount, was 1879.49 ± 13.87 S cm −1, the highest value reported to date.